2012
DOI: 10.1177/1054773812462867
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Community

Abstract: Pulmonary Hypertension (PH) is a complex disorder characterized by elevated pressures in the pulmonary artery that cause right heart failure and eventually leads to death. Treatment regimens can be complex and mortality is high. The purpose of this study was to determine how people with PH are using an online Discussion Board. Qualitative descriptive methodology was used to analyze a convenience sample of self-identified patients with PH. Internet posts to an online Discussion Board from January 1, 2010 to Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Having access to the online community made members feel less alone and provided a reference for what was a normal illness experience [ 17 , 24 , 25 , 29 , 31 , 36 , 40 ]. Members, who often lacked solidarity offline, were able to build a collection of symptoms into a shared identity [ 24 , 25 , 31 , 33 , 34 ]. Offline, members found it difficult to get a real understanding from friends and family and were able to use these online spaces to express these frustrations with a network of people who seemingly understood the challenging nature of self-managing their illness [ 25 , 29 , 34 , 36 , 37 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Having access to the online community made members feel less alone and provided a reference for what was a normal illness experience [ 17 , 24 , 25 , 29 , 31 , 36 , 40 ]. Members, who often lacked solidarity offline, were able to build a collection of symptoms into a shared identity [ 24 , 25 , 31 , 33 , 34 ]. Offline, members found it difficult to get a real understanding from friends and family and were able to use these online spaces to express these frustrations with a network of people who seemingly understood the challenging nature of self-managing their illness [ 25 , 29 , 34 , 36 , 37 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The sharing of condition narratives enabled members the opportunity to reevaluate their situation through lateral and downward social comparison. Being able to see how others coped with their condition reassured members that they could manage their condition through education, adjustment, adaptation, and acceptance [ 17 , 29 , 33 , 35 , 40 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 Patients with PAH or CTEPH are entitled to receive accurate but encouraging information, and healthcare professionals must also communicate their prognosis and, at the appropriate time, provide an opportunity to discuss end-of-life issues. 39 Matura et al 44 found that patients use online peer support on an internet-based PAH discussion board when they seek guidelines and wish to confirm information about PAH or CTEPH. Patients who have experience with PAH or CTEPH could be effective counselors, but the healthcare professionals must also take responsibility for this.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the patients’ knowledge about their disease, their inner feelings, and their external, practical needs during treatment remain important to the patients’ QOL. The qualitative research that has been conducted to date exploring the experience of having PH 7 12 is limited; to our knowledge, no qualitative study of the experience of patients with PH receiving treatment in an Asian setting has been published to date. This study aimed to explore and understand the experiences of patients with PH in Taiwan and also attempted to interpret patients’ experience and needs from a psychiatric perspective, in order to facilitate the formulation of a more specific psychiatric intervention model that meets the needs of patients with PH in the future.…”
Section: Introductionmentioning
confidence: 99%